Validation of the bladder control self‐assessment questionnaire (B‐SAQ) in men. (May 2014) - Sahai, Arun; Dowson, Christopher; Cortes, Eduardo; Seth, Jai; Watkins, Jane; Khan, Muhammed Shamim; Dasgupta, Prokar; Cardozo, Linda; Chapple, Christopher; De Ridder, Dirk; Wagg, Adrian; Kelleher, Cornelius
Abstract : Objective: To validate the Bladder Control Self‐Assessment Questionnaire (B‐SAQ), a short screener to assess lower urinary tract symptoms (LUTS) and overactive bladder (OAB) in men. Patients and Methods: This was a prospective, single‐centre study including 211 patients in a urology outpatient setting. All patients completed the B‐SAQ and Kings Health Questionnaire (KHQ) before consultation, and the consulting urologist made an independent assessment of LUTS and the need for treatment. The psychometric properties of the B‐SAQ were analysed. Results: A total of 98% of respondents completed all items correctly in <5 min. The mean B‐SAQ scores were 12 and 3.3, respectively for cases ( n = 101) and controls ( n = 108) ( P < 0.001). Good correlation was evident between the B‐SAQ and the KHQ. The agreement percentages between the individual B‐SAQ items and the KHQ symptom severity scale were 86, 85, 84 and 79% for frequency, urgency, nocturia and urinary incontinence, respectively. Using a B‐SAQ symptom score threshold of ≥4 alone had sensitivity, specificity and positive predictive values for detecting LUTS of 75, 86 and 84%, respectively, with an area under the curve of 0.88; however, in combination with a bother score threshold of ≥1 these values changed to 92, 46 and 86%, respectively. Conclusions: The B‐SAQ is an easy and quick valid case‐finding tool for LUTS/OAB in men, but appears to be less specific in men than in women. The B‐SAQ has the potential to raise awareness of LUTS. Further validation in a community setting is required.